2021
DOI: 10.3390/molecules26051251
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Lactones and Diterpenes: Promising Therapeutic Candidates for Infectious Diseases, Neoplasms and Other Chronic Disorders

Abstract: Nature is an important source for the discovery of new bioactive compounds. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…In particular, the chemical composition of S. aristata was published by Zdero et al [46] in which beyerene derivatives and other terpenoids were reported. In vitro antiparasitic efficacy has been described for many compounds belonging to these groups [13,[47][48][49]. Interestingly, the effect of the sesquiterpene lactone eupatoriopicrin was determined on an in vivo model of T. cruzi infection [50].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the chemical composition of S. aristata was published by Zdero et al [46] in which beyerene derivatives and other terpenoids were reported. In vitro antiparasitic efficacy has been described for many compounds belonging to these groups [13,[47][48][49]. Interestingly, the effect of the sesquiterpene lactone eupatoriopicrin was determined on an in vivo model of T. cruzi infection [50].…”
Section: Discussionmentioning
confidence: 99%
“…Stevia genus is characterized by the presence of sesquiterpene lactones, diterpenoids and flavonoids, among other phytochemical groups (Borgo et al ., 2021). Anti-parasitic activity has been described for many compounds belonging to these groups (Sanchez Alberti et al ., 2018; Boniface and Ferreira, 2019; Sessa et al ., 2020; Sülsen, 2021). Sesquiterpene lactones are one of the major phytochemical groups of compounds present in the genus Stevia .…”
Section: Discussionmentioning
confidence: 99%
“…Tseng) (Wüpper et al., 2020), and red beet ( Beta vulgaris L.) (Mikolajczyk‐Bator & Kikut‐Ligaj, 2016), imparting them a remarkable bitter taste. Terpenoids are natural compounds derived from isoprene and could be classified into six groups based on their number of carbon atoms: monoterpenes (C10), sesquiterpenes (C15), diterpenes (C20), triterpenes (C30), tetraterpenes (C40), and polyterpenes (C > 40) (Sülsen, 2021). Monoterpenes are volatile aromatic compounds in plants that often constitute parts of the so‐called essential oils, such as limonene, a‐terpinene, and phellandrene (Böttger et al., 2018).…”
Section: Classification Of Bitter Compoundsmentioning
confidence: 99%
“…Due to their various biological effects on human health, plant terpenoids have received growing interest as promising sources of therapeutic agents for many diseases, such as cancer, infection disease, and other chronic disorders (Patlolla & Rao, 2012; Sülsen, 2021). Despite the impoartance of terpenoids in medicine and food science, their sensory properties have been poorly studied, and a better understanding of the molecular basis for their great bitterness is required.…”
Section: Classification Of Bitter Compoundsmentioning
confidence: 99%